Superfluous women : art, feminism, and revolution in twenty-first-century Ukraine - Zychowicz, Jessica, 1982- (2020)
"Superfluous Women tells the unique story of a generation of artists, feminists, and queer activists who emerged in Ukraine after the collapse of the Soviet Union. With a focus on new media, Zychowicz demonstrates how contemporary artist collectives in Ukraine have contested Soviet and Western connotations of feminism to draw attention to a range of human rights issues with global impact. In the book, Zychowicz summarizes and engages with more recent critical scholarship on the role of digital media and virtual environments in concepts of the public sphere. Mapping out several key changes in newly independent Ukraine, she traces the discursive links between distinct eras, marked by mass gatherings on Kyiv's main square, in order to investigate the deeper shifts driving feminist protest and politics today."--
Includes bibliographical references (p. 351-380) and index.
Keywords: Art, Ukrainian -- 21st century; Feminism and art -- Ukraine; Art -- Political aspects -- History -- Ukraine -- 21st century; Feminism -- Ukraine -- History -- 21st century; Women's rights -- Ukraine -- History -- 21st century; Gay rights -- Ukraine -- History -- 21st century